(untitled) (Bangladesh Medical Journal, 2014)
Elderly population needs economic support including food, clothing, medical care, and housing as well as cultural support. In view of the size of the population, scarcity of resources, poverty, insufficient health facilities and absence of strong social security, ageing is going to be a major problem for Bangladesh. Preparing for an elderly population old age and ill-health are inseparable entities to general people. To ensure medical care services separate ward or unit in a hospital should be established for elderly people. Age-friendly Principles for PHC Centres serve as a tool to increase provider awareness and empower older users of PHC centers. There is need for change in the attitude of not only community and the government but also the people. The elderly should be considered not as a burden to society rather their valuable experience should be utilized fruitfully and it should be the responsibility of the society and the government to impart an improved and effective quality of life to them in return for their lifelong dedicated service towards their children and the nation. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18676 Bangladesh Medical Journal 2011 Vol.40(3):48-51